Exploring Bacillus velezensis in a biomedical context: a systematic review - Eduarda Guimarães Sousa; Gabriela Munis Campos; Ludmila Silva Quaresma; Thaís Fernandes Mendonça Mota; Nédia de Castilhos Ghisi; Gabriel Camargos Gomes; Rhayane Cristina Viegas Santos; Beatriz Gamarano Rocha de Souza; Éric Guédon; Siomar de Castro Soares; Joyce da Cruz Ferraz Dutra; Vasco Ariston de Carvalho Azevedo (Academia Molecular Biology and Genomics)
Bacillus velezensis is associated with producing secondary metabolites with antifungal, anti-inflammatory, antagonistic, and antimicrobial activities that have multiple applications in the food industry, agriculture, and farming. This study aims to review current knowledge to highlight the biomedical potential of Bacillus velezensis as a mammalian probiotic supported by in vivo and in vitro research and to compile existing knowledge. All information in this study was searched in the Dimensions, Scopus, PubMed, and Web of Science databases on 2023 Dec 10. The articles were selected according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method and scientometric analysis. A total of 1585 records were identified after the screening process. Of these, 151 were used for scientometric analysis, and 13 were used for data analysis based on in vitro and in vivo studies. The literature review revealed the great biomedical potential of B. velezensis and its relevance in scientific research, especially in recent years, thanks to advances in genome sequencing and the search for alternative antibiotics. The production of secondary metabolites such as surfactin, bacilysin, and fengycin is of growing interest to industry and human health. It also has great probiotic potential due to its antagonistic activity, lack of antibiotic resistance, and immunomodulatory activity. However, the optimization of its use and a better understanding of cultivation methods for gene expression under variable environmental conditions are crucial. Future research should focus on refining cultivation methods and applying techniques to maximize the production of these bioactive compounds to exploit the full potential of B. velezensis in various applications.